Characterizing Skeleton Structure and Stacking Properties of Continuous and Gap Graded Aggregate Mixtures. (12th May 2019) - Bao, Dexiang; Jiaqi, Chen; Wang, Hao; Liu, Huanjiao; Zhang, Jiupeng
Abstract : In order to optimize the skeletal properties of granular pavement materials, a numerical discrete element model for continuous and gap graded aggregate mixtures was developed using a step-by-step filling method. The penetration tests were conducted, and indexes such as penetrating resistance, average coordination number, California bearing ratio, and void ratio of coarse aggregates obtained from the tests were used to evaluate the skeleton structure and the stacking properties of aggregate mixtures. The results show that the skeleton structure of aggregate mixtures is closely related to the combination of particle size. Smaller difference in particle size leads to stronger interference effect. The parameters of stacking properties of continuous and gap graded aggregate mixtures are not significantly different in the natural stacking condition. However, gap graded aggregate mixtures are affected by external loads significantly due to structural reconstruction.